Geographical trend analysis of COVID-19 pandemic onset in Africa - Onafeso, Olumide David (Soc Sci Humanit Open, 2021)
Little has been documented in literature concerning the manner of occurrence and spread of COVID-19 in Africa. Understanding the geographic nature of the corona virus pandemic may offer critical response signals for Africa. This paper employed analysis of variance (ANOVA) to show that significant variations exist among African countries’, particularly total population as well as those using basic drinking water services, gross national income, expenditure on health, number of physicians and air transport passengers. Although we have only considered the number of confirmed corona virus infections noting that the fatality may be too early to discuss, we have relied on data from the European Centre for Disease Prevention and Control (ECDC) to establish a significant association between international mobility based on average annual air passenger carried (r ​= ​0.6) which also successfully predicted (R 2 ​= ​0.501) the number of COVID-19 cases reported in each country along with the population density (R 2 ​= ​0.418). We also detected that COVID-19 cases report y geometrically increased daily x (R 2 ​= ​0.860) with a 2nd order polynomial equation in the form of y ​= ​0.3993 ​× ​2–8.7569 x and a clustered spatial pattern with a nearest neighbour ratio of 0.025 significant at 0.05 α-level. African countries have responded to the pandemic in different ways including partial lockdown, closure of borders and airports as well as providing test centres. We concluded that 40% of Africa are categorized as emerging hot spots while responses differ significantly across regions.